Hybrid Ga-68 prostate-specific membrane antigen PET/MRI in the detection of skeletal metastasis in patients with newly diagnosed prostate cancer: Contribution of each part to the diagnostic performance. Issue 1 (16th November 2022) - Asa, Sertac; Ozgur, Eren; Uslu-Besli, Lebriz; Ince, Burak; Sager, Sait; Demirdag, Cetin; Guner, Ekrem; Sayman, Haluk B.; Bakir, Baris; Sonmezoglu, Kerim
Abstract : Purpose: Bone metastasis is essential in patients with prostate cancer (PCa) as it determines prognosis and survival. Hybrid PET/MRI allows simultaneous acquisition of PET and MRI data, thus combining the strength of both technologies allows the detection of bone marrow metastases that are missed by PET/CT. In this retrospective study, we aimed to evaluate the diagnostic efficiency of hybrid PET/MRI with Ga-68 prostate-specific membrane antigen (PSMA) in detecting skeletal metastases in newly diagnosed PCa patients and compared the effectiveness of stand-alone PSMA PET reviewing versus stand-alone whole-body (WB) MRI evaluation. We also investigated the effect of the interpretation of all PET/MR data together on clinical management. Methods: We studied 74 newly diagnosed PCa patients who underwent PSMA PET/MRI for staging purposes. At first, PET and MRI were evaluated separately for bone lesions on a patient-and-lesion basis and then a further joint PSMA PET/MRI interpretation was made. Results: Patient-based sensitivity, specificity, positive predictive value, negative predictive value and accuracy analysis for bone metastasis was, respectively, 1.0, 0.83, 0.54, 1.0, 0.86 for PET; 0.75, 0.96, 0.81, 0.95, 0.93 for WB MRI and 0.91, 0.95, 0.78, 0, 98, 0.94 for PET/MRI. The combined PET/MRI evaluation changed the clinical impact in 13.5% of patients (eight correct and two wrong decisions) compared to PET stand-alone interpretation. Conclusion: PSMA PET imaging showed superior sensitivity to WB MRI in detecting bone metastases in newly diagnosed PCa patients, whereas WB MRI has superior specificity and PPV. Furthermore, the specificity and PPV of joint PET/MRI evaluation are better than PSMA PET alone. Despite the longer acquisition period, adding WB MRI sequences to PSMA PET imaging appears beneficial for PCa patient management.